THE EFFECT OF TAX SANCTIONS, VEHICLE TAX AMNESTY, AND E-SAMSAT ON THE MOTORISED VEHICLE OF THE TAXPAYER'S COMPLIANCE - Sulistyawati, Ni Wayan; Merkusiwati, Ni Ketut Lely Aryani (Transpublika Publisher, 2024)
Taxpayer adherence refers to an individual's willingness to comply with tax laws and regulations. Meeting the obligation of paying motor vehicle taxes is a significant responsibility for individuals who own vehicles. The main objective of this research is to gather real-life evidence on how tax penalties, PKB amnesty, and E-SAMSAT impact the compliance of motor vehicle taxpayers in Denpasar City. Non-probability sampling, specifically accidental sampling, was used to select 100 participants based on the slovin formula. Data was collected through questionnaires, and multiple linear regression analysis with the SPSS software was used to test the hypotheses. The findings indicate that tax penalties, PKB amnesty, and E-SAMSAT all contribute positively to the compliance of motor vehicle taxpayers in Denpasar City.